Higher education in the United States: Historical excursions - Jack H. Schuster (Revista Electrónica de Investigación Educativa)
Higher education in the United States has been transformed in the last decade as never before in its three hundred years of history. Even though its origin is intimately linked to the religious groups of English settlers, nowadays it is characterized by increasing opportunities of access for students and by a decentralized system which allows institutional diversity. This paper is intended to explain both features by means of a retrospective journey along the main trends of current American higher education; and on the way, a critical review is done of its development, policies, similarities and differences when compared with other countries' higher education.